How Ethical Leadership Promotes Knowledge Sharing: A Social Identity Approach - Wu, Wei-Li (Frontiers in Psychology, 2021)
The aim of this study is to investigate the associations among ethical leadership, group identification, relational identification, organizational identification, and knowledge sharing. This study conducted a survey in Taiwan to collect the data. The administrative group members of schools were invited to participate in this study. The sample included 510 participants, and the hypotheses were tested by using the path analysis and bootstrapping methods in the Mplus program to examine how ethical leadership influences knowledge sharing, through various means of identification. The results of this study show that ethical leadership has both a direct and indirect effect on knowledge sharing. There are two mediating paths in the ethical leadership-knowledge sharing relationship. Firstly, group identification mediates the relationship between ethical leadership and knowledge sharing. Secondly, ethical leadership has an influence on knowledge sharing by means of increased relational and organizational identification. This is a pioneering article that explores the psychological mechanism between ethical leadership and knowledge sharing, using the social identity approach. This study has shown that the social identity theory is a useful and promising perspective for future research studies on ethical leadership-knowledge sharing.